Pemberdayaan Orang Tua dalam Melatih Stimulasi Visual untuk Mengembangkan Kemampuan Kognitif Balita - Oktaviani Cahyaningsih; Dewi Sari Rochmayani (Universitas Pahlawan Tuanku Tambusai, 2026)
Visual stimulation can foster children's cognitive abilities. A poor learning environment can be a trigger for decreased visual acuity in children, even though good vision is crucial for the teaching and learning process. Training motor skills is essential for enhancing brain stimulation and visual acuity, in addition to ensuring good nutrition for children. The methods used in this community service activity are lectures, followed by practice, role-play, and discussions. Parental involvement in visual stimulation is crucial because parents are the first educators for children, so it is necessary to provide appropriate stimulation according to the toddler's developmental stage. Visual stimulation carried out regularly through various simple activities such as reading picture books, playing puzzles, and introducing colors can improve children's attention, memory, classification, problem-solving, and language skills. The evaluation results showed an increase in parental knowledge about visual stimulation, with an average knowledge score before counseling of 62.4 increasing to 85.6 after counseling.